Dithering scientists make a sound profit from loss. - Flusfeder, Helena (Times Higher Education Supplement, 1997)
Describes a method developed by researchers at Tel Aviv University for reducing distortions introduced when CD-quality music is compressed. Discussion on the process of dithering; Experiments on the capabilities of the MMX microprocessor.